A population-based cohort study of rheumatoid arthritis-associated interstitial lung disease: comorbidity and mortality. Issue 10 (13th June 2017) - Hyldgaard, Charlotte; Hilberg, Ole; Pedersen, Alma Becic; Ulrichsen, Sinna Pilgaard; Løkke, Anders; Bendstrup, Elisabeth; Ellingsen, Torkell
Abstract : Objectives: To compare mortality risks in patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD) and patients with RA without ILD. Design: Matched cohort study. Setting: The study was conducted in Denmark, using nationwide, prospectively collected data. Participants: Among patients with RA diagnosed between 2004 and 2016, 679 patients with RA-ILD were matched for birth year, gender and age at RA diagnosis with 11 722 patients with RA but without ILD. Main outcome measures: Mortality risks were assessed using Kaplan-Meier mortality curves, and hazard rate ratios (HRRs) for death were estimated using Cox proportional hazards regression models. Results: The number of prevalent RA patients more than doubled from 15 352 to 35 362 individuals during the study period. RA-ILD was seen in 2.2% of incident RA patients. 34.0% of RA-ILD cases were diagnosed within 1 year prior to and 1 year after the RA diagnosis. One-year mortality was 13.9% (95% CI, 11.4% to 16.7%) in RA-ILD and 3.8% (95% CI, 3.5% to 4.2%) in non-ILD RA, 5-year mortality was 39.0% (34.4% to 43.5%) and 18.2% (17.3% to 19.1%) and 10-year mortality was 60.1% (52.9% to 66.5%) and 34.5% (32.8% to 36.1%), respectively. The HRRs for death were 2 to 10 times increased for RA-ILD compared with non-ILD RA, irrespective of follow-up period. Stratified analysis showed that the HRR for death was highest in the first months after the diagnosis of RA-ILD was made, especially in patients diagnosed with RA before diagnosis of ILD. HRR was higher in males and in patients without comorbidity as assessed by the Charlson Comorbidity Index. Conclusions: ILD is a serious complication in RA, with a significantly increased mortality compared with a large matched cohort of RA comparisons without ILD.